An experience in constructing a three-dimensional geoelectric model based on the results of 2D inversion of magnetotelluric field parameters on an example of the Ingul megablock - Logvinov, I.; Tarasov, V. (S. Subbotin Institute of Geophysics of the NAS of Ukraine, 2013)
Based on dozens of MTS curves involving magnetic variation of parameters 2D inversion of 8 mutually perpendicular profiles covering the area from 30 to 320 ◦E and from 47,8 to 49,50 ◦N was first performed. The obtained results of the simulation were used to construct a three-dimensional model of the geoelectric region using a complex software developed by the authors. The model indicates that the subsoil of the region studied to a depth of 60 km, has got numerous conductivity heterogeneities. The depth of the roof, of the most reliably selected objects, occurs below 6 km. The most conductive parts of objects (with a resistance of less than 10 ohm m and the integral conductivity of more than 50 % of the total) are located at the depths of 20—40 km. The most conductive parts of anomalous objects are consistent with Smelyansk and Bobrinets fracture zones and with their cross-section with Golovanev suture zone.